FORMATION OF THE MARKETING MANAGEMENT SYSTEM OF A TOURIST ENTERPRISE IN MODERN CONDITIONS - BARVINOK, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the issue of the formation of the marketing management system of tourist enterprises in modern conditions of globalization, scientific and technological progress and crisis phenomena. The key stages of marketing activities are defined, including conducting marketing research, determining the purpose, goals and objectives, forming the organizational structure of marketing, developing a marketing strategy and program, implementing marketing activities, control and regulation. Special attention is paid to the complexity of the tourist product, which mostly consists of intangible services, which makes it difficult to promote it on the market.The specifics of the tourist product, in particular its inseparability from the consumption process, variability of quality, ephemerality and seasonality, are analyzed. These properties influence the choice of marketing strategies and tools to ensure the competitiveness of tourism enterprises. The importance of consumer segmentation and marketing research to understand the needs of the target audience, which allows for more effective planning of marketing activities and the creation of a unique tourist product, is especially emphasized.The study also considered the need to adapt marketing strategies to the conditions of the external environment and changes in consumer behavior. The importance of using modern marketing approaches, such as the use of online channels for the promotion of tourist services, the development of loyalty programs and the implementation of advertising campaigns, is outlined. The analysis of external and internal factors of influence allows to optimize the process of making managerial decisions and to promote the stable development of the enterprise in the conditions of a competitive environment.It is proposed to use the concept of Growth mindset to ensure continuous improvement of marketing activities and development of the tourist enterprise. It has been proven that the systematic implementation of this concept helps to increase the flexibility and adaptability of the enterprise, which allows to quickly respond to changes in the external market, increase competitiveness and create unique tourist products that meet the modern requirements of consumers.
Keywords: tourist product; tourist service; tourist enterprise; marketing activity in tourism; marketing management system; marketing management of a tourist enterprise